Eocene to Miocene Out‐of‐Sequence Deformation in the Eastern Tibetan Plateau: Insights From Shortening Structures in the Sichuan Basin. Issue 2 (10th February 2018) - Tian, Yuntao; Kohn, Barry P.; Qiu, Nansheng; Yuan, Yusong; Hu, Shengbiao; Gleadow, Andrew J. W.; Zhang, Peizhen
Abstract: A distinctive NNE trending belt of shortening structures dominates the topography and deformation of the eastern Sichuan Basin, ~300 km east of the Tibetan Plateau. Debate continues as to whether the structures resulted from Cenozoic eastward growth of the Tibetan Plateau. A low‐temperature thermochronology (AFT and AHe) data set from four deep boreholes and adjacent outcrops intersecting a branch of the shortening structures indicates distinctive differential cooling at ~35–28 Ma across the structure, where stratigraphy has been offset vertically by ~0.8–1.3 km. This result forms the first quantitative evidence for the existence of a late Eocene‐Oligocene phase of shortening in the eastern Sichuan Basin, synchronous with the early phase of eastward growth and extrusion of the Tibetan Plateau. Further, a compilation of regional Cenozoic structures reveals a Miocene retreat of deformation from the foreland basin to the hinterland areas. Such a tectonic reorganization indicates that Eocene to Miocene deformation in the eastern Tibetan Plateau is out‐of‐sequence and was probably triggered by enhanced erosion in the eastern Tibetan Plateau. Key Points: A Late Eocene‐Oligocene phase of shortening has been identified in the eastern Sichuan Basin Late Miocene tectonic reorganization occurred in the eastern Tibetan Plateau Late Miocene out‐of‐sequence deformation has been triggered probably by enhanced hinterland erosion